Azithromycin susceptibility testing of Salmonella enterica serovar Typhi: Impact on management of enteric fever. (April 2021) - Skittrall, Jordan P.; Levy, David; Obichukwu, Christian; Gentle, Amy; Chattaway, Marie A.; Hayns, David; Etheridge, Clare; Parry, Christopher M.; Wong, Vanessa; Whitehorn, James
Highlights: Azithromycin susceptibility testing errors can complicate enteric fever management. Testing guidelines do not provide mechanisms to distinguish between causes of error. Control organisms for azithromycin need to differ from those for other antibiotics. Guidelines may not recommend appropriate control organisms for azithromycin. Abstract: Background: Drug-resistant enteric fever is increasingly common in the Indian subcontinent. Correctly determining azithromycin resistance matters where drug-resistant enteric fever is common and oral therapy necessary. Case report: In two patients returning from Pakistan to the UK with cephalosporin-resistant Salmonella enterica serovar Typhi, gradient strip testing erroneously indicated azithromycin resistance; the errors were detected by repeat testing and confirmed by whole genome sequencing. Results: Both patients were treated with meropenem and, when revised susceptibility results were known, with azithromycin, allowing a switch to oral therapy. Conclusion: As cephalosporin resistance becomes more common, azithromycin will be key for treating enteric fever and optimizing practice in susceptibility testing will be crucial. Practitioners should be aware of key steps to minimize error in azithromycin susceptibility testing, and should be alert for possible errors when reported azithromycin resistance is discordant with known prevalence of resistance.